COVID-19 and The Holy Land of Lalibela World Heritage Site, Ethiopia - Dagnachew Nega; Balew Baye; Amare Kindu (International Journal of Religious Tourism and Pilgrimage, 2022)
Ethiopia is the home of many tourist sites. Among these is Lalibela, one of the most famous and most visited World Heritage Sites. However, due to the COVID-19 pandemic, the tourism industry was severely affected. Thus, the main objective of the study is to investigate the impacts and solutions for the prevalence of COVID-19 at the holy land of Lalibela, the World Heritage Site. The study followed descriptive research design. The target population of the study were the local communities, religious fathers, local tourist guides, culture and tourism experts and hotel workers. The research was conducted through non-probability sampling techniques. Convenience sampling and purposive sampling methods were used. The results illustrate that economic impacts, social impacts and psychological impacts were major issues that COVID-19 has caused for the Holy Land of Lalibela, the World Heritage Site. As per the findings, mechanisms to overcome the effects of COVID-19 on the community and the tourism sector include promotion, giving attention to sustainable follow up, developing new products, facing the challenges of seasonality and applying the rules and regulations approved by the World Health Organization. Thus, the tourism and hospitality stakeholders in the area need to strongly integrate and give attention to minimise the effect of COVID-19 on the tourism industry at Lalibela.